Multi agent Community to support information processing in Wireless Sensor Network applications. (24th February 2010) - Hla, Khin Haymar Saw; Choi, YoungSik; Park, Jong Sou
One of the key challenges of applications concerning with Wireless Sensor Network (WSN) is finding suitable and timely information in the dynamic environment. To address these issues, this paper proposes to employ multi agent community by combined used of intelligent sensors and middle agent architecture. The idea is to use intelligent sensor as a service provider agent that announces for the active events and middle agent as a directory facilitator that assists in locating the service providers with the information requesters in the dynamic WSN environment. Simulation results have approved that proposed system enhances the information searching time, reduces the service discovery cost and communication cost.